High-Fat Diet-Induced Fatty Liver Is Associated with Immunosuppressive Response during Sepsis in Mice. (8th December 2021) - Wang, Fangzhao; Cen, Zhongran; Liu, Zhanguo; Gan, Jianwei; Zhang, Xianglong; Cui, Qianru; Gong, Shenhai; Chang, Ping; Chen, Peng
Abstract : High-fat diet-induced fatty liver is an indolent and chronic disease accompanied by immune dysfunction and metabolic disturbances involving numerous biological pathways. This study investigated how this abnormal metabolic disorder influences sepsis in mice. Mice were fed with normal chow (NC) or high-fat diet (HFD), and palmitic acid (PA) was used to treat hepatocytes to mimic fat accumulation in vitro . Lipopolysaccharide (LPS) was used to induce sepsis and related immune responses. Mice fed on a high-fat diet displayed higher mortality and more severe liver damage but compromised immunoreaction. The supernatant from PA-treated primary hepatocytes markedly diminished the inflammatory cytokine expression of macrophages after LPS stimulation, which showed a state of immunosuppression. Metabolomics analysis indicated the level of many key metabolites with possible roles in immunoreaction was altered in the HFD and PA groups compared with corresponding controls; specifically, β -hydroxybutyric acid (BHB) showed an immunosuppressive effect on Raw264.7 cells during the LPS stimulation. Transcriptomic analysis suggested that several differential signaling pathways may be associated with the alteration of immune function between the NC and HFD groups, as well as in the in vitro model. Our study suggests that the consumption of HFD may alter the hepatic metabolic profile, and that certain metabolites may remold the immune system to immunosuppressive state in the context of sepsis.